MANAGEMENT OF MASTITIS IN POST PARTUM: LITERATURE REVIEW - susanti susanti; Ulpawati Ulpawati; Novi Yulianti (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Mastitis is inflammation of the breast that may be caused by a bacterial infection. Infection is a phenomenon that often occurs in breastfeeding mothers, mastitis certainly requires immediate and appropriate treatment, and mastitis that is not handled properly can affect breastfeeding. This study aims to review the management of mastitis. Delayed, inappropriate and inadequate treatment of mastitis can lead to recurrence, more extensive breast lesions, and even tissue damage. Mastitis is most common in the second and third weeks postpartum, with most reports indicating that 74% to 95% of cases occur within the first 12 weeks. However, it can occur at any stage of lactation, including the second year. Mastitis and breast abscess occur in all populations, whether the mother is breastfeeding or not. The reported incidence varies from a few to 33% of breastfeeding women but is usually under 10%. The results show that clinical observation that mastitis is caused by stagnation of milk in the breast, and that efficient ejection of milk as it forms can largely prevent the condition (Gunther, 1958). Therefore, breastfeeding contests are the most important part of mastitis treatment, and in cases of mastitis, breastfeeding should still be given with the correct breastfeeding technique. Antibiotics and symptomatic treatment can make a woman feel better temporarily, but if the milk output is not corrected, the condition can get worse or even if antibiotics are given.